Bass guitar - Pfeiffer, Patrick (--For dummies., 2020)
Whether you've never held a bass before or you're looking to improve your skills, this resource is a complete guide to playing bass guitar. Pfeiffer provides fresh, updated practice lessons, teaching techniques, and access to online sample tracks to hone your skills.